Methodology of fiscal audit in minimizing fiscal risks - nedjar, ayoub (Journal of Research in Finance and Accounting, 2022)
This study aims to show the role of fiscal audit in controlling fiscal risks, as economic institutions are suffering from the heavy tax burden and the obligation to comply with the tax laws in force, which are characterized by complexity, diversity and instability. . This study concluded the importance of the fiscal audit as a mechanism to reduce fiscal risks, as the auditor, through the mission message, verifies the company’s commitment to depositing its tax declarations within the legal deadlines, while calculating all taxes and fees that must be paid on the one hand, and the extent to which it exploits the fiscal privileges granted by the fiscal legislature from On the other hand, the fiscal auditor within the company can identify potential fiscal risks and make recommendations to avoid them.